Preoperative biological therapy and short-term outcomes of abdominal surgery in patients with inflammatory bowel disease. Issue 3 (22nd May 2012) - Waterman, Matti; Xu, Wei; Dinani, Amreen; Steinhart, A Hillary; Croitoru, Kenneth; Nguyen, Geoffrey C; McLeod, Robin S; Greenberg, Gordon R; Cohen, Zane; Silverberg, Mark S
Abstract : Objective: Previous investigations of short-term outcomes after preoperative exposure to biological therapy in inflammatory bowel disease (IBD) were conflicting. The authors aimed to assess postoperative outcomes in patients who underwent abdominal surgery with recent exposure to anti-tumour necrosis factor therapy. Design: A retrospective case-control study with detailed matching was performed for subjects with IBD with and without exposure to biologics within 180 days of abdominal surgery. Postoperative outcomes were compared between the groups. Results: 473 procedures were reviewed consisting of 195 patients with exposure to biologics and 278 matched controls. There were no significant differences in most postoperative outcomes such as: length of stay, fever (≥38.5°C), urinary tract infection, pneumonia, bacteraemia, readmission, reoperations and mortality. On univariate analysis, procedures on biologics had more wound infections compared with controls (19% vs 11%; p=0.008), but this was not significant in multivariate analysis. Concomitant therapy with biologics and thiopurines was associated with increased frequencies of urinary tract infections (p=0.0007) and wound infections (p=0.0045). Operations performed ≤14 days from last biologic dose had similar rates of infections and other outcomes when compared with those performed within 15–30 days or 31–180 days. Patients with detectable preoperative infliximab levels had similar rates of wound infection compared with those with undetectable levels (3/10 vs 0/9; p=0.21). Conclusion: Preoperative treatment with TNF-α antagonists in patients with IBD is not associated with most early postoperative complications. A shorter time interval from last biological dose is not associated with increased postoperative complications. In most cases, surgery should not be delayed, and appropriate biological therapy may be continued perioperatively.